The Paradox of Indonesian Sovereignty, 1945-1949 - Hariyono, Hariyono; Wijaya, Daya Negri; Kurniawan, Bayu; Jr, Fernando A. Santiago (History Department, Semarang State University and Historian Society of Indonesia, 2024)
Abstract: This paper aims to elucidate Indonesian sovereignty post-1945 independence. Employing a historical approach, it delves into historical occurrences based on various pertinent sources, be they primary or secondary. The paper underscores Indonesia's upholding of autonomy through a national revolution, placing it among nations that secured independence after the Second World War. The Republic of Indonesia encountered internal and external hurdles over a prolonged span of five years. The amalgamation of diverse political-military factions in Indonesia was marred by discord and sporadic outbursts of violence. This state of affairs was exacerbated by Allied forces seeking to reinstate the pre-World War II global political status quo and the Netherlands' desire to reassert control over Indonesia. A blend of conflict and diplomacy pursued by the Republic of Indonesia reached an accord at the Netherlands–Indonesian Round Table Conference, acknowledging the nation's sovereignty. Nevertheless, the aspirations of the national founding figures for economic self-sufficiency and political authority remained unfulfilled post-independence. Hence, a decolonization process entwined with the neo-colonialism phenomenon stands as imperative. Abstrak: Tulisan ini bertujuan untuk menjelaskan kedaulatan Indonesia pasca kemerdekaan 1945. Dengan menggunakan pendekatan historis, makalah ini menggali kejadian-kejadian historis berdasarkan berbagai sumber yang relevan, baik sumber primer maupun sekunder. Makalah ini menggarisbawahi penegakan otonomi Indonesia melalui revolusi nasional, yang menempatkan Indonesia di antara negara-negara yang berhasil meraih kemerdekaannya setelah Perang Dunia Kedua. Republik Indonesia menghadapi rintangan internal dan eksternal dalam kurun waktu lima tahun. Penggabungan berbagai faksi politik-militer di Indonesia dirusak oleh perselisihan dan ledakan kekerasan yang sporadis. Keadaan ini diperparah oleh pasukan Sekutu yang ingin mengembalikan status quo politik global sebelum Perang Dunia II dan keinginan Belanda untuk menegaskan kembali kendali atas Indonesia. Perpaduan antara konflik dan diplomasi yang diupayakan oleh Republik Indonesia mencapai kesepakatan dalam Konferensi Meja Bundar Belanda-Indonesia, yang mengakui kedaulatan negara. Namun demikian, aspirasi para tokoh pendiri bangsa untuk kemandirian ekonomi dan otoritas politik tetap tidak terpenuhi pasca kemerdekaan. Oleh karena itu, proses dekolonisasi yang terkait dengan fenomena neo-kolonialisme menjadi sangat penting.